Climate and the Oceans - Vallis, Geoffrey K. (Book collections on Project MUSE., 2012)
The oceans exert a vital moderating influence on the Earth's climate system. They provide inertia to the global climate, essentially acting as the pacemaker of climate variability and change, and they provide heat to high latitudes, keeping them habitable. Climate and the Oceans offers a short, self-contained introduction to the subject. This illustrated primer begins by briefly describing the world's climate system and ocean circulation and goes on to explain the important ways that the oceans influence climate. Topics covered include the oceans' effects on the seasons, heat transport between.